2000
DOI: 10.1208/pt010207
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of pramlintide degradation in aqueous solution as a function of temperature and pH

Abstract: The stability of the 37− amino acid peptide pramlintide, in aqueous solution, was studied as a function of pH and temperature. Samples of pramlintide formulated as a parenteral product were exposed to elevated temperatures and to realistic storage conditions for as long as 30 months. Pramlintide degradation was monitored by three high-performance liquid chromatography (HPLC) methods: a reversedphase (RP-HPLC) and a strong-cation exchange (SCX-HPLC) method for percentage purity determination by area normalizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…Since the activation of both receptors might be advantageous for maximal efficacy on food intake and body weight, we prioritized initially non-selectivity. We found that formulation at pH 7 caused chemical instability including deamidation of asparagine residues, as reported for pramlintide, , and this could not be solved by formulations or minor pH adjustments. In order not to deviate too much from h-amylin, formulation at low pH seemed necessary, and we initiated a third branch of the program focused on the chemical stability at neutral pH to secure the option of co-formulation with other peptides.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…Since the activation of both receptors might be advantageous for maximal efficacy on food intake and body weight, we prioritized initially non-selectivity. We found that formulation at pH 7 caused chemical instability including deamidation of asparagine residues, as reported for pramlintide, , and this could not be solved by formulations or minor pH adjustments. In order not to deviate too much from h-amylin, formulation at low pH seemed necessary, and we initiated a third branch of the program focused on the chemical stability at neutral pH to secure the option of co-formulation with other peptides.…”
Section: Resultssupporting
confidence: 59%
“…An initial concern was that attachment of a lipophilic fatty acid would increase intermolecular attractive forces, causing an even higher propensity to form amyloid fibrils. Additionally, published data on pramlintide , suggested a need for improvement of chemical stability, primarily targeting deamidation of asparagine residues to enable formulation at neutral pH.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies identified 5° C as a suitable long-term storage condition for pramlintide injection and 25° C as an appropriate storage condition during a 1-month patient-use period [ 10]. The drug product vials, however, may experience temperature excursions (both above and below the recommended storage conditions) during patient use, or product shipping and warehousing.…”
Section: Discussionmentioning
confidence: 99%
“…The RP-HPLC method for determining pramlintide potency and m-cresol concentration has also been previously described [10]. Visual inspection of the vials was conducted per procedures in USP 23-NF 18 to detect the presence of any extraneous matter such as cores or fragments from the rubber stoppers.…”
Section: Test Methodsmentioning
confidence: 99%
See 1 more Smart Citation